2021
DOI: 10.14202/vetworld.2021.1788-1796
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bone marrow mesenchymal stem cell transplantation on tumor necrosis factor-alpha receptor 1 expression, granulosa cell apoptosis, and folliculogenesis repair in endometriosis mouse models

Abstract: Background and Aim: Endometriosis affects the ovaries and causes a decrease in the oocyte quality during endometrial receptivity. During the development of ovarian follicles, paracrine communication occurs between granulosa cells and oocytes. This study was conducted to determine the effects of bone marrow mesenchymal stem cell transplantation on tumor necrosis factor-alpha (TNF-α) receptor 1 (TNFR1) expression, granulosa cell apoptosis, and folliculogenesis in endometriosis mouse models. Materials and Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…The obtained results showed that BMSC‐CM therapy could mitigate nitro‐oxidative stress and consequently improved blastocyst development and quality in EMS mice. Our observation is in line with the findings of Dwiningsih et al's study, which indicated that BMSC exert protection on EMS by suppressing inflammation and apoptosis in granulosa cells and supporting folliculogenesis in EMS mouse models 21 . Additionally, we recently indicate that BMSC‐CM supplementation during maturation improved IVM, fertilization, and the subsequent development of EMS‐induced oocytes 12 .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The obtained results showed that BMSC‐CM therapy could mitigate nitro‐oxidative stress and consequently improved blastocyst development and quality in EMS mice. Our observation is in line with the findings of Dwiningsih et al's study, which indicated that BMSC exert protection on EMS by suppressing inflammation and apoptosis in granulosa cells and supporting folliculogenesis in EMS mouse models 21 . Additionally, we recently indicate that BMSC‐CM supplementation during maturation improved IVM, fertilization, and the subsequent development of EMS‐induced oocytes 12 .…”
Section: Discussionsupporting
confidence: 92%
“…Our observation is in line with the findings of Dwiningsih et al's study, which indicated that BMSC exert protection on EMS by suppressing inflammation and apoptosis in granulosa cells and supporting folliculogenesis in EMS mouse models. 21 Additionally, we recently indicate that BMSC-CM supplementation during maturation improved IVM, fertilization, and the subsequent development of EMS-induced oocytes. 12 Indeed, BMSC-CM provides a variety of pro-inflammatory cytokines, growth factors, and anti-apoptotic and antioxidant substances, and we were not able to determine the actual levels of these factors in plasma.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…To determine the sample size, the Lemeshow formula was used, with the result that each group consisted of 16 mice. 15 The making of endometriosis model mice was in accordance with what was done in the study by Hendarto. 16 In the present study, the presence of endometriosis was confirmed by the formation of endometriotic lesions and visually visible hypervascularization of the peritoneal tissue at surgery.…”
Section: Methodsmentioning
confidence: 89%